Large Mammals Occupancy in Geothermal Power Plant Activities - Aji, Bakhtiar; Kusrini, Mirza Dikari; Rahman, Dede Aulia (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Geothermal as one of renewable resources, provide alternative to address the ever-increasing energy demand. Most of the sources are located in forest ecosystem, on which ecological impact took place. PT Supreme Energi Rantau Dedap (SERD) is geothermal power plant project located in protected forest of Bukit Jambul Gunung Patah, South Sumatera. To investigate the large mammal’s species richness and its occupancy, the research observe data from SERD camera trap data installed during exploration and construction phases. Data are then analyzed with single season occupancy modelling with habitat changes (distance), light and elevation as the impact parameters. There are 13, out of 14, large mammals that captured by the camera trap and one was identified on direct encounter. Mostly, the best occupancy model is with constants covariate. Hog badger and muntjac constantly apparent as high occupancy both in naïve occupancy and model result. Four species occupancies are affected by geothermal power plant activity, they are: surili, forest pig, tapir and hog badger. The result showed that during the development phase, large mammals still inhabited the powerplant area despite the fact that some species responded negatively against the impact. Meanwhile, during the construction phase the species richness is tend to be higher but the detection level is lower with varied occupancy level for each large mammals’ species.